Researching with teachers with disabilities in Tanzania: adaptations and observations - Hennessy, Sara (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12752114 ZenodoArchiveConcept: 12752113 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1036 10.53832/edtechhub.1037 2405685:Q75XZHT7
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Introducing the EdTech Hub’s programme for research in low-income countries – The EdTech Hub - Hennessy, Sara (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:A7H9CPGD A7H9CPGD
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Advancing evidence-based decision making in LMICs: Focus of EdTech Hub’s work - Hennessy, Sara (EdTech Hub, 2021)
This blog sets out the Hub’s aims and approaches to identifying appropriate and effective uses of EdTech that can potentially raise learning outcomes in low- and middle-income countries (LMICs). Research shows that EdTech offers immense potential, but sustainable and positive change at scale has largely proved elusive in practice – particularly for marginalised learners where we focus our work. To…
KerkoCite.ItemAlsoKnownAs: 2405685:33PABHJH 2405685:Q8R8G8WG
Keywords: _EdTechHub_Output

Teachers and Technology in Rural Malaysian Classrooms: Insights from the T4 Teachers and Technology Global Survey - James, Cynthia; Hennessy, Sara (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16760930 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1134 ZenodoArchiveConcept: 16760929
Keywords: _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
ZenodoArchiveID: 5652080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652080 2339240:VJNSF4EV 2339240:Z6ZIBS2B 2405685:6E2K4GGE
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

School Infrastructure Survey - Adam, Taskeen; Koomar, Saalim; Hennessy, Sara (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5866554 2405685:VIFG4IFF
Keywords: _comingsoon; _r:AddedByZotZen

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
DOI 10.53832/edtechhub.0147 ZenodoArchiveID: 7652491 ZenodoArchiveConcept: 7652490 2405685:ECXPS38I KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8363989 10.53832/edtechhub.0174 2405685:ECXPS38I 2405685:MDC3E34G
Keywords: _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Publisher: Net Journals ERIC Number: EJ1373064 KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.104.22.048 10.5281/zenodo.5863400 10.53832/edtechhub.0097 2339240:6EFQH53V 2339240:7QAZINAG 2405685:49EBMKRI 2405685:GXZHRRYW 2405685:YXFLNITE
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Leveraging Technology for Scaling Teacher Professional Development: Insights into Usage, Challenges, and Opportunities in Rural Tanzania - Swai, Calvin; Hennessy, Sara; Chachage, Kristeen; Koomar, Saalim; Adam, Taskeen; Mtenzi, Fredrick (EdTech Hub, 2026)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17029055 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1137 ZenodoArchiveConcept: 17029054
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

International experiences with intergrating interactive whiteboards: Policy, practice, pedagogy and professional development - Hennessy, Sara (Life in schools and classrooms: past, present and future, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:A5JRV6W2 2405685:C3E7HA3U

Bridging between research and practice: Supporting professional development through collaborative studies of classroom teaching with technology - Hennessy, Sara (Sense Publishers, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory – through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators’ complementary professional knowledge bases. Teachers’ voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially. The book reflects upon the power of lesson video review and details how the co-inquirers negotiated “intermediate theory” – bridging educational theory and specific settings – framed in mutually accessible language and embodied in interactive multimedia resources for teacher development. These include video clips, analytic commentary from multiple perspectives, lesson materials, plus optional prompts for reflection and critique – not models of “best practice”. The resources make pedagogy explicit and vividly illustrate the book’s ideas, offering theory-informed yet practical tools designed with and for practitioners. Hennessy and colleagues have tested a model of ongoing, teacher-led development and innovation, professional dialogue and classroom trialing stimulated by discussing selected multimedia resources. The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes – springboarding teachers’ further critique and professional learning. “I cannot recommend this book too highly … it weaves a complex developmental story with a range of facets. It emphasises clearly the rigour of the research that was conducted, while demonstrating the complexity of the inter-relationships, practices and issues for both teachers and researchers in developing practical and theoretical knowledge. Its graphic insights through text and associated media provide exemplars for teachers and those who work with teachers as a rich resource. It shows us all what can be achieved and the means of achieving it.” Prof. Barbara Jaworski, University of Loughborough
KerkoCite.ItemAlsoKnownAs: 2405685:TSJ3FNKZ 2534378:F6KIMYGG

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SNH4JG9L EdTechHub.Source: 2339240:94ZP3EK4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3624978 2129771:SNH4JG9L 2339240:94ZP3EK4 2339240:VMNDUZSF 2405685:2GLWRD86
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Problem Analysis. A Global Public Good produced by the EdTech Hub - Hennessy, Sara; Jordan, Katy; Haßler, Björn; Hollow, David; Brugha, Meaghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (EdTech Hub, 2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
EdTechHub.Copy: 2129771:9VXUZISD EdTechHub.Copy: 2129771:ADGISTZU EdTechHub.ThisIsNot: 2339240:2387P995 2339240:8RA9UD7W shortDOI: 10/ghgnfz KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2129771:56GZ7UBP 2129771:9VXUZISD 2129771:ADGISTZU 2129771:GYTVIZJV 2129771:MBZLFNDM 2339240:2387P995 2339240:65KP6SVQ 2339240:6FUA4SDV 2339240:85SBE7SC 2339240:8RA9UD7W 2339240:IXIRDBKK 2339240:STPRNPV3 2405685:BBQI3VSA 2405685:CMRISZHV 2405685:F6UAIKKN 2405685:QJTH2UXC 2405685:R88UVQZ7 503888:7EH7BANW 503888:PI9FLM7C
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Technology use for teacher professional development in low- and middle-Income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 10.5281/zenodo.4733147 2339240:5GVQGQC4 2339240:GQEBFNI2 2339240:LPFYJHUF 2339240:Q5369EBL 2405685:66IBMGWS 2405685:E5J2KHF2 2405685:KXGE9JIR 2405685:P4MI8J9M 2405685:R3SISS58 2405685:RKQI4W3A 2405685:T5QVE96Z 2534378:5CCARHUH 2534378:DZ4AXQJ2 4042040:V58GV3BA
Keywords: Disability; ICT; Read; Referenced; Teacher education and training; Teacher professional development; What works evidence; _EdTechHub_Output; _MELA_knowledge_product; _MELA_seen; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology; ⛔ No DOI found

Gender and disability-related influences on teachers’ access to technology-mediated professional learning in Tanzania - Hennessy, Sara; Chachage, Kristeen; Swai, Calvin; Koomar, Saalim; Singal, Nidhi; Massam, Winston; Paskali, Jonathan H.; Adam, Taskeen (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15591957 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1121 ZenodoArchiveConcept: 15591956
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SLHSYDRF PreviousDOI: 10.5281/zenodo.3377829 PreviousShortDOI: 10/ghgngc KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3377828 10.5281/zenodo.3377829 10.5281/zenodo.3595482 10/ghgngc 2129771:84AIHEAJ 2129771:Q74CFTXR 2129771:SLHSYDRF 2339240:2DHE9CQC 2339240:BF96YT5K 2339240:FJZA9NPX 2339240:NLMLQD75 2405685:6YT2AIMC 2405685:7S8Z2IUF 2405685:RUSE8WYV
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
ZenodoArchiveID: 7691834 ZenodoArchiveConcept: 7691833 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7434218 10.5281/zenodo.7691834 10.53832/edtechhub.0148 2405685:GXM765F3
Keywords: _r:AddedByZotZen

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
ZenodoArchiveID: 7701270 ZenodoArchiveConcept: 7701269 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7701270 10.53832/edtechhub.0149 2405685:6V4DBZR8
Keywords: _r:AddedByZotZen

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.
KerkoCite.ItemAlsoKnownAs: 2339240:TTB8Z79I 2405685:HQG3IHPW 6018420:4TZJWG3F

Reimagining Teacher Professional Development for Scalable, Sustainable and Equitable Outcomes - Using EdTech Research Evidence - Hennessy, Sara; Koomar, Saalim (2021)
KerkoCite.ItemAlsoKnownAs: 2405685:8NPXTAKN

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1096 ZenodoArchiveConcept: 14901417
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Usawa na maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Chachage, Kristeen; Swai, Calvin; Rwambali, Innocent; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Chuo Kikuu cha Dodoma, Chuo Kikuu cha Aga Khan, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza upanuzi na mabadiliko ya kuendana na mahitaji ya walimu na mazingira ya shule katika utekelezaji wa Mafunzo Endelevu ya Walimu Kazini (MEWAKA) unaojumuisha matumizi ya teknolojia. Katika kuandaa zana hizi, tumetumia zana zilizochapishwa katika awamu ya kwanza ya utafiti huu na mifano kutoka sehemu mbalimbali, kwa kuzingatia mifano mizuri ya utafiti kuhusu elimu. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901456 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1097 ZenodoArchiveConcept: 14901455
Keywords: _r:AddedByMyEducationEvidence

Usawa na Maamuzi ya Walimu katika Mafunzo ya Walimu yanayosaidiwa na Teknolojia nchini Tanzania Muhtasari wa Mapendekezo ya Kisera ya Awamu ya Pili [Rasimu] - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Paskali, J.H.; Mtenzi, Fredrick; Komba, Aneth; Jacob Mrope, Winifrida; Anthony, Gervace; Malibiche, Mustapha; Mrosso, Vicky; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17392468 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1144 ZenodoArchiveConcept: 17392467
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 10.17863/cam.54714 2339240:6LGJJU8F 2339240:MVL3KA6H 2339240:U3SHRB68 2339240:XZDCXAZ7 2405685:8WKWEBZZ 2405685:A5XKUF3W 2405685:CHDUKI36 2405685:VJ8U5IDE 2405685:YENK6ASB
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, Hannah; Hennessy, Sara; Pimmer, Christoph (Research Papers in Education, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/02671522.2022.2034925 2405685:ZFPJ7TP7

The relationship between educational television and mathematics capability in Tanzania - Watson, Joe; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2021)
Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low-income countries when delivered in controlled settings. However, existing research in low-resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of normal television exposure. This paper, therefore, investigates the relationship between normal exposure to a popular Tanzania-produced cartoon, Ubongo Kids and mathematics capability, as represented by plausible values derived from an item response theory model applied to children’s test responses. Cross-sectional investigation of a sample of 38 682 Tanzanian children suggested normal educational television exposure to be significantly associated with mathematics capability, when controlling for age, sex, school enrolment, Kiswahili attainment and household fixed effects. While cross-sectional results are not necessarily causal, the findings in this paper broadly correspond with those from previous designs using repeated observations. What is more, considering association results alongside cost and viewership estimates suggests television-based interventions to be highly cost effective. Practitioner Notes What is already known about this topic National data for Tanzania suggests the country to have both low levels of mathematics proficiency and considerable access to television technology. Educational television-based interventions might, therefore, be worthy of consideration by educational policymakers, especially given that studies conducted in controlled settings indicate that television can deliver learning benefits. There is, however, little evidence concerning educational television exposure outside of controlled settings. Only one such study in a low-income context that concerned the association between learning outcomes and viewing among primary-age children has been identified. What this paper adds This paper addresses this dearth of research by investigating the association between normal exposure to a Tanzanian cartoon, Ubongo Kids and mathematics capability, as derived from an item response theory model applied to the test responses of 38 682 children. Cross-sectional findings suggest the association between normal television exposure and mathematics capability to be significant. Further, a cost-effectiveness comparison with alternate interventions in comparable contexts indicates that educational television is highly cost-effective. Implications for practice and/or policy The findings presented in this paper concerning educational television viewership in usual environments act to triangulate those from prior research conducted in controlled settings. As such, policymakers in low-income contexts now possess more convincing evidence on the potential influence of educational television interventions. Additionally, the cost-effectiveness comparison made suggests that educational television should be considered a viable option by policymakers seeking to address learning outcomes with limited resources.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13047 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 2339240:7RAS7H3N 2405685:MVRBU5UB
Keywords: Tanzania; cost effectiveness; educational television; mathematics

Using interactive whiteboards to orchestrate classroom dialogue - Mercer, Neil; Hennessy, Sara; Warwick, Paul (Technology Pedagogy and Education, 2010)
KerkoCite.ItemAlsoKnownAs: 2339240:WD8VBWA9 2405685:EVX6UTWW

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Pedagogic change by Zambian primary school teachers participating in the OER4Schools professional development programme for one year - Hennessy, Sara; Haßler, Björn; Hofmann, R. (Research Papers in Education, 2016)
Supporting and upskilling teachers are essential to enhancing the quality of learning in developing contexts – the focus of Education For All – yet little evidence exists concerning what kinds of teacher education are actually most effective and what changes in ‘quality’ are desired and feasible. This paper illustrates how a concrete, research-informed school-based, model of professional development in sub-Saharan Africa can address the quality agenda. It reports on a trial of a pioneering, multimedia programme supporting interactive mathematics and science teaching using open educational resources and classroom digital technology, where available. The programme was carefully adapted to the Zambian context and ran weekly for one school year with 12 teachers in a low-resourced primary school. The study examined the impact on teachers' thinking and classroom practices. Data were derived from observations, lesson and workshop recordings, teacher interviews, portfolios and audio diaries. Through a teacher-led workshop approach and trialling new pedagogical strategies, teachers raised their expectations of pupils, adapted to learners’ knowledge levels, used more practical and group work, and integrated technology use. Pupils built deeper understanding of subject matter, were actively engaged, worked collaboratively and used digital technologies for problem-solving.
shortDOI: 10/gftr46 KerkoCite.ItemAlsoKnownAs: 10.1080/02671522.2015.1073343 10/gftr46 10/ghgnfx 2129771:4DDI7MD4 2129771:CPWUEHPK 2129771:DLXY6Q8J 2129771:QGHFB3QL 2129771:WHB6UUT9 2339240:8PZIPSBY 2339240:ASBRKMNU 2339240:UTDG7DWR 2339240:VBAD27XQ 2405685:C677I5RF 2405685:CHHQANDG 2405685:CSCFPKV2 2405685:F6292I9Z 2405685:LDKZC9TP 2405685:NAJLZ3FE 2405685:NK5HW6CV 2405685:R5KQR27A 2405685:S9FRC57W 2405685:VZ562RQX 2405685:YBR4RYHA 2534378:4NJUGCID 2534378:E2PEHWQT 2534378:GGBWWEIN 2534378:HQ26LIRW 2534378:QVE8VZAZ 2534378:Z7EEHWT2 257089:AGK9WB3X 257089:FXEJEAA9 261451:ENUVRNA2 261495:4NPFWURU 261495:YIZHH9Z5
Keywords: C:sub-Saharan Africa; CAREER development; EDUCATION – Study & teaching; GRADUATE education; PROFESSIONAL education; TEACHER training; ZAMBIA; Zambia; __:import:01; __:match:final; __:matched; __:study_id:2099887; ___working_potential_duplicate; __finaldtb; digital technology; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Teacher factors influencing classroom use of ICT in sub-Saharan Africa - Hennessy, Sara; Harrison, David; Wamakote, Leonard (Itupale Online Journal of African Studies, 2010)
This paper synthesises the research literature on teachers‟ use of Information and Communication Technology (ICT) in primary and secondary schools in sub-Saharan Africa, with a particular emphasis on improving the quality of subject teaching and learning. We focus on the internal factors of influence on teachers‟ use, or lack of use, of technology in the classroom. Our discussion attends to perceptions and beliefs about ICT and their motivating effects, technological literacy and confidence levels, pedagogical expertise related to technology use, and the role of teacher education. These factors are discussed in light of significant infrastructure and other external issues. We conclude by drawing out a number of pedagogical implications for initial teacher education and professional development to bring schooling within developing contexts into the 21 st century.
EdTechHub.Copy: 2129771:J94BQM7C KerkoCite.ItemAlsoKnownAs: 2129771:J94BQM7C 2339240:957DANTW 2405685:RXIW5GY7
Keywords: Schools; Secondary; Scientific literature; ⛔ No DOI found

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=111289127&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2015.1092466 10/gfv5xz 2129771:L2HUHYLN 2339240:24LHAF5C 2339240:K9R22K2F 2339240:WV3XY5NW 2405685:6ZLKKKH7 2405685:8V49PM4G 2405685:KILQYYBU 2405685:SXKPQUJ5 2534378:6TMRG3EP 2534378:BF6PBW3F 2534378:QQ6BVI89
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, Hannah; Hennessy, Sara; Pimmer, Christoph (Research Papers in Education, 2022)
KerkoCite.ItemAlsoKnownAs: 10.1080/02671522.2022.2034925 2405685:ZFPJ7TP7

Methodology for literature reviews undertaken by the EdTech Hub - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Sara Hennessy; David Hollow; Katy Jordan; Kevin Martin; Mary Murphy; Hannah Walker (EdTech Hub, 2019)
An output of the EdTEch Hub
EdTechHub.Copy: 2129771:3GKL5PCI EdTechHub.Copy: 2129771:L2EAYWTN shortDOI: 10/ghgnfq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352101 10.5281/zenodo.3595594 10/ghgnfq 2129771:3GKL5PCI 2129771:K4IV67YV 2129771:L2EAYWTN 2317526:NRY5DISC 2339240:LY57CR53 2339240:XNCNITQP 2405685:BMM3Z3CM 2405685:CEJDF5XI
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _dont_post_PDF; _yl:h; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Phase 2 Round 2 Recommendations - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15388175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1118 ZenodoArchiveConcept: 15388174
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10652003 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1013 ZenodoArchiveConcept: 10652002
Keywords: _r:AddedByMyEducationEvidence

OER4Schools: Outcomes of a sustained professional development intervention in Sub-Saharan Africa - Haßler, Björn; Hennessy, Sara; Hoffmann, R; Makonga, Abel (Frontiers in Education, 2020)
Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention showed that the programme became self-sustaining; earlier participants reported further development of their interactive teaching strategies and awareness of pupil progress; recent joiners developed similarly. Roles of teachers and pupils changed and a new classroom culture emerged. The study identifies the key mechanisms involved in sustainability, including culturally sensitive and participatory development and implementation, semi-structured multimedia materials, and supportive organisational structures for sustained professional learning. Our findings are hence framed by sociocultural influences as well as the wider policy context.
HHH3A shortDOI: 10/ghgn5x KerkoCite.ItemAlsoKnownAs: 10.3389/feduc.2020.00146 10/ghgn5x 2129771:6KN48Q7A 2339240:A5GQ37WB 2339240:B8J5VSFY 2405685:BG6WTIJK 2405685:BNF58PFR 2405685:KLUBUEJY 2405685:V7S2E5AQ 2405685:VHZVRENG 2534378:M3FT5RN4
Keywords: Author:Haßler; C: Zambia; Culturally responsive pedagogy (CRP); Design-based implementation research; Interactive Pedagogy; Learner-centred pedagogy; School leadership; Sustainable Development Goal (SDG) 4; Teacher Profesisonal Development; Zambia; ___working_potential_duplicate; _yl:b; dode_eth-src-dode; dode_eth-trf2-dode; school improvement; sub-Saharan Africa

Recommendation 7: Use ICT to provide access to content, professional development and professional learning communities - Lawrie, J.; Hennessy, Sara; Haßler, Björn; Phalachandra; Lawrie, J. (Where it's needed most: Quality professional development for all teachers, 2015)
EdTechHub.Source: 2129771:KQGAREE9 EdTechHub.Source: 2129771:KQGAREE9 KerkoCite.ItemAlsoKnownAs: 2129771:KQGAREE9 2405685:PKLI25VA
Keywords: C:Fragile contexts; dode_eth-src-dode; dode_eth-trf2-dode

Developing dialogic classroom practices through supporting professional agency: Teachers’ experiences of using the T-SEDA practitioner-led inquiry approach - Calcagni, Elisa; Ahmed, Farah; Trigo-Clapés, Ana Laura; Kershner, Ruth; Hennessy, Sara (Teaching and Teacher Education, 2023)
Classroom dialogue is considered productive for learning but rarely observed, and practitioner professional development is needed. This study investigated how 67 teachers across educational phases in six countries contextualised the T-SEDA inquiry toolkit to conduct classroom inquiries and develop new practices. Surveys and inquiry reports yielded insights into how practitioner agency was further developed, with implications for sustainability. Change was evident in self-reported enhanced awareness and understanding of dialogue and use of dialogic strategies. Increases in students’ dialogic participation and plans for dissemination to colleagues were reported.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2023.104067 2405685:ZQQP3GIM
Keywords: Classroom dialogue; Dialogic teaching; Professional development; Professional learning; Reflective inquiry; Teacher agency

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
A global survey of teachers’ responses to the Covid-19 pandemic
KerkoCite.ItemAlsoKnownAs: 2339240:L9HFYFBK 2339240:PG5K4YH4 2339240:VJ8NQRB8 2405685:452IQSGM 2405685:8993UPBX 2405685:SMFP44X2

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7CKKU8RW 2405685:L43R48P2

Technology use in teacher preparation and professional development in low-and middle-income countries - UNESCO Digital Library - Hennessy, Sara; D'Angelo, Sophia; Koomar, Saalim; Kreimeia, Adam; Adam, Taskeen; Cao, Lydia; Haßler, Björn (UNESCO, 2023)
https://doi.org/10.54676/NJZV8067 KerkoCite.ItemAlsoKnownAs: 2339240:9URXV92S 2405685:UU8FCJCF

OER4Schools: Participants Book - Hennessy, Sara; Haßler, Björn; Blair, Janet; Duggal, Nitu; Shin Leong, Wei; Makonga, Abel; Tembo, Agness (The Centre for Commonwealth Education, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:58TW376N 2405685:FBGNRJ43
Keywords: dode_eth-src-dode; dode_eth-trf2-dode

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2339240:EYQWGP5R 2405685:ZGFQHAS3

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 2339240:JZZE3QML 2405685:8XNNJ8S9
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.caeo.2022.100080 2339240:WQ3SA2IB 2405685:JTHYW3X4
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

MEWAKA in Tanzania: Emerging findings on tech-supported teacher professional development - Koomar, Saalim; Massam, Winston; Anthony, Gervace; Mrope, Winifrida; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fredrick; Proctor, Jamie; Komba, Aneth; Mwakabungu, Fika; Barretto, Johnpaul; Barretto, Winston Massam, Gervace Anthony, Winifrida Mrope, Taskeen Adam, Sara Hennessy, Fredrick Mtenzi, Jamie Proctor, Aneth Komba, Fika Mwakabungu and Johnpaul, Saalim Koomar (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teachers’ Continuous Professional Development (TCPD)) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The programme is decentralised, with teacher learning based in schools and focused on semi-structured Communities of Learning (CoLs). CoLs are spaces where teachers can gather weekly to discuss and reflect on issues most relevant to their schools as well as learn and improve their pedagogical skills. Peer facilitators help teachers to collaboratively solve problems, learn new approaches to improve their practice, and generally create a culture of reflection and school improvement.
KerkoCite.ItemAlsoKnownAs: 2339240:AQZAQSU7 2405685:KMN7H8UA

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen